Vida Saludable: ¡Reconozca el fraude! - Jennifer Hillan; Linda B. Bobroff (EDIS)
This revised 1-page handout is the Spanish language version of FCS8585/FY096: Healthy Living for Elders: Spotting Quackery Word Search. It was written by Jennifer Hillan and Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, September 2011.